DEVELOPMENT OF A WEB-BASED NEW STUDENT ADMISSION INFORMATION SYSTEM - Akmal Hidayat; A. Sriwana Army; Ahmad Abdillah Fathur Rachman; Muhammad Nur Ilham; Muhammad Ihsan Arif (Jurusan Pendidikan Teknik Elektro, 2024)
Admission of new students is a routine activity carried out by schools every new school year. This activity aims to advance the school so that in its implementation a selection is needed. This selection is carried out in order to achieve a target of achieving the quality of prospective students. In this new student admission, a committee is needed to facilitate the activity. Currently, not many schools in Indonesia have implemented an online admission system. The purpose of this research is to design a web-based new student admission information system